China Economic Relations with Developing Countries in Africa. A Critical Literature Review - Kariuki, Robert Kariuki (Journal of International Relations and Policy, 2022)
Purpose: Although not yet a superpower, China has propelled itself to both challenges and the existing status quo that has brought it into direct competition with other superpowers. The overall objective of this study was to examine china economic relations with developing countries in Africa. Methodology: The paper used a desk study review methodology where relevant empirical literature was reviewed to identify main themes and to extract knowledge gaps. Findings: This study concluded that hat the changes in China Africa relations were informed by the shifting of bilateral relations from 1989-2003. The shifts of bilateral relations were informed by the change of regimes. Economic engagement between China and Africa during the period 1977-1990, accounted for these foreign aid, economic and technical cooperation between both countries. During this period, the Tolbert and Doe's administrations accounted for China Africa economic engagement. From the findings, the Doe and Taylor regimes severed bilateral relations with China which accounted for low economic interaction between China and Africa developing countries from 1989 to 2003. Unique Contribution to Theory, Policy and Practice: This study recommended that it would be necessary for the African government to create a comprehensive strategy that would effectively balance its relations with China and the West. In addition, the African government needs to unleash its full potential and establish a policy for long-term development that corresponds with the interests of its citizens.